Multiphase Reactors : Reaction Engineering Concepts, Selection, and Industrial Applications - Harmsen, Jan; Bos, René (De Gruyter graduate., 2023)
This Multiphase Reactors book is about fundamentals, selection, design, development (scale-up) and applications of two- and three-phase reactors. It is a graduate textbook focused on creating understanding of the fundamentals, as much as possible without resorting to mathematics. It also is full of real-life industrial applications and examples from the authors' own experiences. The target audience comprises students and industrial practitioners who may or may not have had formal training in chemical reaction engineering. Each chapter explains the subject and contains take home messages, examples, worked out cases, quiz questions, and exercises.